UPAYA GURU TAHFIDZ DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA DI SMA IT AL-USWAH SIGLI - Abdullah Ali; Syarifah Rahmi; Fuad Fuad (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
This research is a field research with descriptive qualitative research type. Sources of data in this study were school principals, tahfidz teachers and students. The data collection technique uses observation, interview, and documentation techniques. And data analysis techniques using the Miller and Huberman techniques, namely data reduction, data presentation and drawing conclusions or verification. To test the validity of the data, source triangulation and technique triangulation were used. And the results of the research show that students' ability to memorize the Al-Qur'an varies. This is due to their different intelligence abilities. There are students who memorize quickly and according to the knowledge of recitation, there are students who are slow in memorizing but they understand the science of recitation, and there are also students who are lacking in both, namely slow memorization and do not understand the laws of recitation. As for the efforts of the tahfidz teacher in improving students' memorization of the Qur'an, namely: the existence of cooperation between the teacher and the school principal, providing tahsin and tahfidz learning, providing motivation, giving assignments and using various methods. There are two factors that cause the obstacles faced by tahfidz teachers in increasing students' memorization of the Al-Qur'an, namely internal factors including different student abilities, no motivation in memorizing the Al-Qur'an, lazy muraja'ah memorization, and conditions physical condition of students and teachers, and external factors including lack of support from family or parents at home.